Minha experiência no curso de medicina da UFSCar - Nascimento, Ana Claudia Paesani (Universidade Federal de São Carlos, 2024)
The political pedagogical project of the UFSCar medical school requires a Course Completion Work that summarizes the student's trajectory. Thus, this work aims to demonstrate my experiences and learning process during medical school throughout the three educational cycles, based on my personal impressions regarding the constructivist learning method and my contact with teachers, preceptors and patients who had a big impact on my journey.
My experience during UFSCar medical school
Keywords: Metodologia ativa; Constructivist learning; Relato de experiência; Critical reflection; Formação médica; Medical school; CIENCIAS DA SAUDE::MEDICINA